The Accidental Alchemist - Pandian, Gigi 1975- (Woodbury, Minnesota : Midnight Ink, 2015)
Former alchemist Zoe, hoping to leave her old life behind her, is instead forced back into it when she discovers a dead man on her porch and a gargoyle stow-away in her new house.
"Includes recipes!"--Page 4 of cover.
Keywords: Alchemists -- Fiction; Gargoyles -- Fiction; Murder -- Investigation; Fiction; Mystery fiction; Fantasy fiction